Positive Parenting Program to Improve Mother Efficacy in Parenting Teenagers - Silvia Wulandari; Tina Afiatin (Faculty of Psychology, Universitas Gadjah Mada, 2020)
Parenting efficacy is essential in parenting quality. This study aimed to devise and determine the Positive Parenting Program effect in improving the parenting efficacy of mothers with teenage children. The study tested two hypotheses. First, the Positive Parenting Program had good content validity. Secondly, the Positive Parenting Program could improve the parenting efficacy of mothers. The study involved 27 mothers subjects (13 subjects of the experimental group and 14 subjects of the control group). The experiment was carried out using the method of ‘Untreated control group design with dependent pretest and posttest samples’ involving three measurements at pretest, posttest, and follow-up. The results proved that the Positive Parenting Program Module had good content validity. The module has a high content validity with Aiken's V coefficients in each session ranging from 0.89 to 0.95 with an average of 0.92. The second hypothesis test was performed by Mann Whitney U Test analysis. The results of the study also showed that the Positive Parenting Program significantly improved the parenting efficacy of mothers (Zposttest-pretest= -4,321, p = 0.001 (p <0.05), Zfollow-pretest= -4,423, p = 0.001 (p <0,05)).